Tributos municipales del Gobierno Autónomo Descentralizado del Cantón Montalvo y su incidencia en la ejecución presupuestaria del periodo 2023. - Maya Monar, Ángel Miguel (2024)
This curricular integration project will focus on conducting a thorough analysis of the impact of municipal taxes from the decentralized autonomous government of the Montalvo canton (hereinafter GADM of the Montalvo canton) on the budget execution for the year 2023. Proper management of public monetary resources is essential to ensure sustainable development for the entire community, providing quality basic services and infrastructure. The development of this research will include background information from previous studies related to municipal taxes and budget execution variables. Additionally, theoretical references will outline concepts and definitions from national and international authors related to tax collection, taxes, and budgeting. The methodology used in this curricular integration project is based on a mixed and descriptive method, combining qualitative and quantitative approaches to gather information and establish a comprehensive understanding of our study variables. The analysis of these variables allowed us to determine our study population, which consists of various financial department employees of the GADM of the Montalvo canton. Information collection techniques include interview questionnaires and structured observation, designed to gather objective data and subjective insights from the involved individuals. The central issue of this research focuses on how low municipal tax collection affects budget execution. This led to the formulation of the following hypothesis: "How does the collection of municipal taxes influence the increase in budget execution in the decentralized autonomous government of the Montalvo canton?"